Mathematics Education and Language Diversity The 21st ICMI Study - Barwell, Richard; Clarkson, Philip; Halai, Anjum; Kazima, Mercy; Moschkovich, Judit; Planas, Núria; Setati-Phakeng, Mamokgethi; Valero, Paola; Villavicencio Ubillús, Martha (New ICMI Study Series, 2016)
This book examines multiple facets of language diversity and mathematics education. It features renowned authors from around the world and explores the learning and teaching of mathematics in contexts that include multilingual classrooms, indigenous education, teacher education, blind and deaf learners, new media and tertiary education. Each chapter draws on research from two or more countries to illustrate important research findings, theoretical developments and practical strategies. This open access book examines multiple facets of language diversity